Experiences of tourists with intellectual disabilities: A phenomenological approach. (September 2021) - Gillovic, Brielle; McIntosh, Alison; Cockburn-Wootten, Cheryl; Darcy, Simon
Abstract: This paper aims to explore ways in which adults with intellectual disabilities experience tourism. The study applies phenomenology and draws on in-depth interviews with participants with intellectual disabilities focusing on their lived experiences of tourism. The tourism experience was significant and meaningful to the participants, in that tourism provided a sense of 'normality, ' encouraged self-efficacy, and strengthened relational connections. This paper advances theory by conceptualising the nature of the tourism experience through the authentic voices and lived experiences of adults with intellectual disabilities. This lens of intellectual disability addresses a scarcity of representation in existing tourism scholarship, augmenting and advancing inclusive understandings of tourism experiences for these individuals with disabilities. Highlights: Dispels misconceptions that people with intellectual disabilities cannot and do not travel. Advances understandings of the tourism experience for people with intellectual disabilities. Travel provides a sense of normality, learning, and relational connections. Contributes original understanding of the plurality of lived experiences of disability. Applies a phenomenological approach to offer authentic voices and embodied experiences.